Engaging with policy actors and the discursive politics of school-related gender-based violence in Ethiopia and Zambia. Issue 4 (4th July 2021) - Johnson Ross, Freya; Parkes, Jenny
ABSTRACT: School-related gender-based violence (SRGBV) has received growing attention in policy and practice over the past decade, increasingly attended to in national and international contexts. Yet we need to understand more fully the processes and actors through which this policy enactment takes place. This article analyses the understanding of SRGBV by policy stakeholders in Ethiopia and Zambia. It shows how the concept is discursively stretched by actors in positive ways, as well as shrunk and fixed in ways that limit its application, in gendered and political processes. We propose SRGBV offers a point where contestation between policy actors and sectors is inevitable. Opportunities for dialogue that include recognition of the everyday and gendered manifestations of violence may offer a contribution to facilitating policy enactment that moves towards a holistic and inclusive account of SRGBV.